Rules for Performing Arithmetic Operations - Husenova Dilora Mirzayevna (Euro Asian Journal Publishing, 2024)
This article outlines the fundamental rules for performing arithmetic operations, including addition, subtraction, multiplication, and division. It covers essential properties such as commutativity, associativity, and the identity elements that govern each operation. The article also discusses the order of operations, commonly referred to as PEMDAS, which ensures the correct sequence of calculations when multiple operations are involved. By following these rules, one can achieve accuracy and consistency in mathematical computations, providing a solid foundation for more advanced mathematical concepts and problem-solving
Keywords: arithmetic operations; addition